Somatization and Psychosomatic Symptoms - Koh, Kyung Bong. (Springer New York : Imprint: Springer, 2013)
In these uncertain and disquieting times, clients presenting with stress problems are on the rise. Common, too, are those pains that refuse to go away--stomachaches, chest pains, and headaches that fall through the diagnostic cracks and resist appropriate interventions. Somatization and Psychosomatic Symptoms brings theoretical clarity and frontline expertise to these challenging cases, offering integrative approaches and clinical tools. This comprehensive reference addresses not only the assessment and treatment of chronic physical complaints but also explores the mechanisms that underlie them, expanding on current perspectives to create a biopsychosociocultural lens for practice. Specific symptoms and disorders are examined in depth, including stress-induced cardiomyopathy, post-stroke depression, and fibromyalgic pain. On the practice side, chapters review a gamut of interventions (from relaxation and mindfulness to systems and cognitive-behavioral), the therapeutic relationship, and the latest findings from psychopharmacology. Included in the coverage: A comparison of somatoform disorders with depressive and anxiety disorders. Genes, memes, culture, and psychosomatic medicine: an integrative model. Complementary and alternative treatment in psychosomatic medicine. Pain, depression, and anxiety: a common language of suffering. Motivational interviewing in psychosomatic medicine. Cancer: a psychosomatic perspective. With its innovative takes on mind-body medicine, Somatization and Psychosomatic Symptoms will enhance the work of a wide range of professionals, among them psychiatrists, physicians, health and clinical psychologists, and rehabilitative medicine specialists.